Upaya Peningkatan Kompetensi Pemuda Melalui Pelatihan Menulis Proposal Kegiatan di Desa Margosari, Kendal - Firmansyah, Asep (IAIN Syekh Nurjati Cirebon, 2023)
Youth are agents of change or individuals who have more energy, enthusiasm and potential to carry out many activities. Therefore, young people often have the initiative to do something to improve their environment or are involved in an activity/project, including being involved in an activity in the village government through a forum called Karang Taruna. This is like what exists in Margosari Village, Kendal. To make an activity/project a success, it is necessary to start with a design or concept that can provide an explanation to all parties involved. The design or concept in formal form is called a proposal. This research aims to determine the impact of activity proposal writing training on young people in Margosari Village who are not yet skilled at compiling or writing activity proposals. The method used in this research is descriptive analytical with data collection techniques in the form of questionnaires. The results of the research stated that initially there were still many participants who were unable to write proposals, namely 14 people and 4 people who could not. Meanwhile, there were 15 participants who lacked knowledge about proposals with indications of not knowing or not knowing about the types of proposals. After the training, it was shown that all participants expressed their understanding of writing proposals. This was reinforced by the statements of 13 participants who admitted that they could write a proposal if their understanding was later applied in making the proposal, while 6 people stated that they were not sure. Meanwhile, from the open questionnaire, 16 people stated that there were no shortcomings at all and that the training was very useful.